2019
DOI: 10.1021/acs.analchem.8b05723
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Integrity of Gas-Phase Conformers of Sodiated 25-Hydroxyvitamin D3 by Drift Tube, Traveling Wave, Trapped, and High-Field Asymmetric Ion Mobility

Abstract: Quantitation of the serum concentration of 25-hydroxyvitamin D is a high-demand assay that suffers from long chromatography time to separate 25-hydroxyvitamin D from its inactive epimer; however, ion mobility spectrometry can distinguish the epimer pair in under 30 ms due to the presence of a unique extended or “open” gas-phase sodiated conformer, not shared with the epimer, reducing the need for chromatographic separation. Five ion mobility mass spectrometers utilizing commercially available IMS technologies,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…From a fundamental perspective, CCS differs from m/z information as it is a conditional value derived from an ion's mobility (K) and depends on properties of the ion, such as size or charge state, as well as the buffer gas, temperature and the field strength-to-pressure ratio 19 . However, it is well-established that ionization, ion transfer and ion separation can also influence the observed ion structure and hence the ion's mobility, e.g., via formation of protomeric isomers 19,42 , other types of open/closed conformers 43 or metastable solvent clusters 44 . In combination, this influences the comparability of CCS values and the question to which extent CCS reference values can be established and used independently of the instrument type is still under discussion 45 .…”
mentioning
confidence: 99%
“…From a fundamental perspective, CCS differs from m/z information as it is a conditional value derived from an ion's mobility (K) and depends on properties of the ion, such as size or charge state, as well as the buffer gas, temperature and the field strength-to-pressure ratio 19 . However, it is well-established that ionization, ion transfer and ion separation can also influence the observed ion structure and hence the ion's mobility, e.g., via formation of protomeric isomers 19,42 , other types of open/closed conformers 43 or metastable solvent clusters 44 . In combination, this influences the comparability of CCS values and the question to which extent CCS reference values can be established and used independently of the instrument type is still under discussion 45 .…”
mentioning
confidence: 99%
“…Some interlaboratory studies have also included the comparison of CCS measurements carried out by different IMS technologies (i.e., DTIMS, TWIMS, TIMS). , However, although theoretically possible, it is not so obvious that a single CCS database can be applied to commercial platforms based on different IMS technologies. Hinnenkamp et al have compared the DT CCS N 2 and TW CCS N 2 of 124 protonated molecules and related sodium adducts.…”
mentioning
confidence: 99%
“…Inter-platform studies should also consider different IMS forms (i.e., DTIMS, TWIMS, TIMS) to establish if standardized CCSs can be implemented in all of them or whether, on the contrary, DT CCS, TW CCS and TIMS CCS values must be reported and used. In general, similar CCS values are provided by these three IMS technologies when using the same buffer gas as observed for the sodium adduct of 25-hydroxyvitamin D3 [134]. However, another recent study about the CCS of 35 pharmaceuticals, 64 pesticides, and 25 metabolites of pesticides has shown that, although the majority of ions present differences lower than 1.1% between DT CCS and TW CCS values, both values cannot be compared in all cases [135].…”
Section: Current Perspectives Of Ion Mobility Spectrometrymentioning
confidence: 71%